A COMPARATIVE ANALYSIS OF EDUCATIONAL TERMINOLOGY IN ENGLISH AND UZBEK LANGUAGES (Ustozlar uchun, 2025)
This article examines the linguistic features of educational terminology in English and Uzbek languages, focusing on the semantic, morphological, and functional aspects of key terms. The study analyzes the origin, adaptation, and usage of educational terms in both languages, as well as the influence of globalization and English dominance in modern education. Using comparative linguistic and semantic analysis, the paper highlights how English terms are integrated into the Uzbek language system and how Uzbek maintains its own morphological identity in the process.